Effect of varying operating conditions on cathode surface roughness using guar as a smoothing agent in copper electrowinning - Mkhawana, Nhlamulo (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.